2018
DOI: 10.31234/osf.io/7g3xc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing ovulatory cycle shifts in women’s preferences for men’s behaviors

Abstract: The existence of ovulatory cycle shifts in women’s mate preferences has been discussed controversially. There is evidence that naturally cycling women in their fertile phase, compared to their luteal phase, evaluate specific behavioral cues in men as more attractive for sexual relationships. However, recent research has cast doubt on these findings. We addressed this debate in a large, pre-registered within-subject study including salivary hormone measures and luteinizing hormone tests. One-hundred-fifty-seven… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…For these reasons, we do not think that our data and results, nor the results reported by Gangestad et al, are in favor of the ovulatory shift hypothesis. Indeed, the null results of our study are in line with other, recently published, large-scale replication studies investigating cycle shifts in preferences for masculine faces (Dixson et al, 2018;Jones et al, 2018;Marcinkowska et al, 2018a), bodies (Marcinkowska et al, 2018a;van Stein et al, 2019), voices (Jünger et al, 2018b) and behaviors (Stern, Gerlach, & Penke, 2019). Drawing null conclusions from just our data would be premature.…”
Section: The Problem Of Unfalsifiabilitysupporting
confidence: 86%
See 1 more Smart Citation
“…For these reasons, we do not think that our data and results, nor the results reported by Gangestad et al, are in favor of the ovulatory shift hypothesis. Indeed, the null results of our study are in line with other, recently published, large-scale replication studies investigating cycle shifts in preferences for masculine faces (Dixson et al, 2018;Jones et al, 2018;Marcinkowska et al, 2018a), bodies (Marcinkowska et al, 2018a;van Stein et al, 2019), voices (Jünger et al, 2018b) and behaviors (Stern, Gerlach, & Penke, 2019). Drawing null conclusions from just our data would be premature.…”
Section: The Problem Of Unfalsifiabilitysupporting
confidence: 86%
“…Importantly, many of the researchers of recently published studies investigating ovulatory cycle shifts (Dixson et al, 2018;Jones et al, 2018;Jünger et al, 2018a;Stern et al, 2019) opened their data, allowing for in-depth evaluations of the conducted analyses and the conclusions put forward, as shown in the current debate. However, all studies for which open data were provided reported no compelling evidence for the ovulatory shift hypothesis.…”
Section: Showcase For the Importance And Helpfulness Of Open Sciencementioning
confidence: 99%
“…Looking at current literature on ovulatory changes in general, the predominant finding is that women show increased sexual motivation when they are fertile (Arslan, Schilling et al, 2018; Bullivant et al, 2004; Jones et al, 2019; Roney & Simmons, 2013, 2016; Shirazi et al, 2019). While the nature and function of these shifts remain a matter of debate (Arslan, Schilling et al, 2018; Gangestad et al, 2005; Havliček et al, 2015; Pillsworth et al, 2004; Pillsworth & Haselton, 2006; Stern et al, 2019, 2020), one hypothesis that is gaining more attention and empirical support is the motivational priority shifts hypothesis (Roney, 2016; Roney & Simmons, 2013). According to this hypothesis, estradiol and progesterone act as a two-signal code that promotes mating effort during the fertile phase, when reproductive fitness benefits outweigh the costs (risking injury, sexually transmitted diseases and opportunity costs with regard to e.g.…”
Section: Discussionmentioning
confidence: 99%
“…FERTILITY AND KIN 5 Second, many studies in this literature have employed between-subjects (i.e., cross-sectional) designs, which are ill-suited for testing subtle ovulatory shifts in behaviors that have substantial between-subject variance (Gangestad et al, 2016;Jones et al, 2018a). Importantly, large-scale within-subject (i.e., longitudinal) studies that used more objective methods to assess women's hormonal status (e.g., measuring sex hormones from saliva) have generally not replicated previously reported findings for ovulatory shifts in mate preferences (Jones et al, 2018a;Jünger et al, 2018a;Jünger et al, 2018b;Marcinkowska et al, 2018).…”
mentioning
confidence: 92%